Effect of vibration on reciprocating sealing performance. (February 2023) - Wei, Wang; Liu, Hao; Guo, Chenhao; Jiang, Haoyi; Ouyang, Xiaoping
Abstract: Reciprocating seals are widely used and are subject to vibration in most applications. However, the vibration model of the reciprocating seal has not been established, and the law of the vibration effect on the sealing performance has not been revealed. In this paper, a radial sinusoidal vibration transient model of the reciprocating rod seal is established for the first time, including the vibration model, 3-D finite element model, and mixed lubrication model. Based on the established model, the macroscopic contact pressure and leakage characteristics under different fundamental vibration amplitudes (FVAs) and frequencies (FVFs) are analyzed, revealing the effects of vibration on sealing performance for the first time. Simulation results show that with a fixed FVA, the leakage rate is maximum at the resonance point and decreases as the FVF moves away from the resonance frequency. With a fixed FVF, an increase in FVA will increase the net leakage rate over the vibration period.